UPAYA PEMBERDAYAAN KADER DALAM PEMANFAATAN BAHAN PANGAN LOKAL UNTUK PENCEGAHAN ANEMIA PADA IBU HAMIL - Mahmudah, Mutik; Utami, Uji; Wigunantiningsih, Ana; Noviani, Aris; Hastutik, Hastutik (Jurnal Pengabdian Multidisiplin dan Pemberdayaan Masyarakat, 2025)
Anemia in pregnant women is a public health problem that has serious impacts on both mothers and babies, including increasing the risk of childbirth complications, premature birth, low birth weight, and high maternal neonatal morbidity and mortality. Anemia prevention efforts have focused largely on iron supplementation, but additional strategies based on nutrient rich local foods are needed. This community service activity aims to empower Posyandu cadres through education on the use of local foods such as sweet potatoes, moringa leaves, and spinach in preventing anemia. The methods used included lectures, interactive discussions, and the use of leaflets as educational media. A total of 23 cadres participated in the activity with a pre test, counseling, and post test. The evaluation results showed an increase in knowledge, attitudes, and behavior of cadres. Good knowledge increased from 7 people (30.4%) to 17 people (73.9%). Good attitudes increased from 10 people (43.5%) to 15 people (65.2%), while good behavior increased from 7 people (30.4%) to 13 people (56.5%). This increase demonstrates a close relationship between cadre knowledge, attitudes, and behavior in anemia prevention efforts. Therefore, empowering cadres through local food-based education has proven effective and can be a sustainable strategy for improving maternal health at the community level. Kata kunci: pemberdayaan, kader, pangan lokal, anemia